Chromosome-Level Analysis of the Pelochelys cantorii Genome Provides Insights to Its Immunity, Growth and Longevity - Xiaoli Liu; Haiyang Liu; Yakun Wang; Mingzhi Li; Liqin Ji; Kaikuo Wang; Chengqing Wei; Wei Li; Chen Chen; Lingyun Yu; Xinping Zhu; Xiaoyou Hong (Biology, 2023)
The Asian giant soft-shelled turtle, Pelochelys cantorii (Trionychidae), is one of the largest aquatic turtles in China and was designated as a First-Grade Protected Animal in China in 1989. Previous investigation based on a combination of Illumina short-read, PacBio long-read and Hi-C scaffolding technologies acquired a high-quality chromosome-level genome of Pc. cantorii. In this study, comparative genomic analysis between Pc. cantorii and 16 other vertebrate genomes indicated that turtles separated from the ancestor of archosaurians approximately 256.6 (95% highest posterior density interval, 263.6–251.9) million years ago (Mya) (Upper Permian to Triassic) and that Pc. cantorii separated from the ancestor of Pd. sinensis and R. swinhoei approximately 59.3 (95% highest posterior density interval, 64.3–54.3) Mya. Moreover, several candidate genes, such as VWA5A, ABCG2, A2M and IGSF1, associated with tumor suppression, growth and age were expanded, implicating their potential roles in the exceptional longevity of turtles. This new chromosome-level assembly has important scientific value in the study of conservation of Pc. cantorii and also enriches the evolutionary investigation of turtle species.